Extract of moringa seeds as sugarcane juice flocculant - Gravatim Costa, Gustavo Henrique [UNESP] (2016)
The objective of this work was to evaluate extractive agents for proteins of moringa (Moringa oleifera) seeds, and the coagulant effect of this protein extract on sugarcane juice for sugar production, which uses acrylamide polyelectrolytes. The extractors were deionized water, and KCl and MgCl2 solution at 0.1, 0.5, 1.0, 1.5, and 2.0 mol L-1. The protein extracts were used for sedimentation of sugarcane juice in 11 doses. The solutions of 0.1 mol L-1 MgCl2 and 1.0 mol L-1 KCl were the most effective in protein extraction. The KCl 1.0 mol L-1 dose, at 500 mg L-1, results in clarified juice with better chemical-technological characteristics.